Hubungan Antara Psychological Hardiness dan Acculturative Stress pada Mahasiswa Indonesia yang Merantau ke Luar Negeri - Suhandi, Levinna; Witarso, Laurentius Sandi (MANASA, 2025)
Indonesian students studying abroad often face various challenges during their adaptation process, which can lead to acculturative stress. Psychological hardiness is a key factor that may help reduce this stress. It is a personality trait that enables individuals to cope with stress by viewing challenges as opportunities for growth and maintaining commitment and control in difficult situations. This study aimed to examine the relationship between psychological hardiness and acculturative stress among Indonesian students abroad. A quantitative method with correlational analysis was used, involving 140 Indonesian students who had been studying abroad for no more than two years as of October 2024. Data were collected using the Hardiness Scale and the Acculturative Stress Scale for International Students (ASSIS). The results revealed a negative correlation (-.313) between psychological hardiness and acculturative stress. Specifically, the control (-.358) and challenge (-.321) dimensions of psychological hardiness were also negatively correlated with acculturative stress. These findings suggest that students with higher psychological hardiness perceive themselves as capable of managing their environment and see change as a positive experience, which reduces stress. Future research is recommended to further explore the role of psychological hardiness in reducing acculturative stress among international students.